2016
DOI: 10.1084/jem.20151000
|View full text |Cite
|
Sign up to set email alerts
|

A neuroprotective role for microglia in prion diseases

Abstract: Microglial activation is a hallmark of most neurodegenerative disorders, yet it is not clear if it plays beneficial or deleterious roles. Zhu et al. provide evidence for a general protective role of microglia in the pathogenesis of prion diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
96
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 121 publications
(102 citation statements)
references
References 44 publications
4
96
2
Order By: Relevance
“…It has recently been demonstrated that activation of microglia contributes an over-all protective role against prion pathology, probably by phagocytosing harmful prion aggregates or cellular debris28. Our observation of shortened clinical duration in Neil3 KO mice could therefore be a result of compromised microglial activation in this genotype.…”
Section: Discussionmentioning
confidence: 55%
“…It has recently been demonstrated that activation of microglia contributes an over-all protective role against prion pathology, probably by phagocytosing harmful prion aggregates or cellular debris28. Our observation of shortened clinical duration in Neil3 KO mice could therefore be a result of compromised microglial activation in this genotype.…”
Section: Discussionmentioning
confidence: 55%
“…Microglia also play a role in autoimmune demyelination (experimental autoimmune encephalomyelitis [EAE]), with a specific role in clearing myelin debris (37). Notably, microglia differed phenotypically and in terms of microglia phagocytosis has been demonstrated in the context of prion disease, in which microglia depletion resulted in accelerated disease progression, probably due to diminished prion clearance (57).…”
Section: Discussionmentioning
confidence: 99%
“…The same ex vivo model was used to determine the effect of microglial depletion on prion-induced neurodegeneration. After microglial depletion, not only PrP Sc accumulation but also neurotoxicity of prions were drastically enhanced, and prion pathology was markedly aggravated (47). Moreover, while the tga20/ CD11b-HSVTK transgenic mice were intracerebrally infected with prions, followed by implantation of osmotic minipumps containing ganciclovir to deliver the drug directly into the brain, the incubation time of prion-infected microglia-depleted mice was significantly shortened (47).…”
Section: Microglial Activation and Cytokine Release In Prion Diseasesmentioning
confidence: 99%
“…Moreover, while the tga20/ CD11b-HSVTK transgenic mice were intracerebrally infected with prions, followed by implantation of osmotic minipumps containing ganciclovir to deliver the drug directly into the brain, the incubation time of prion-infected microglia-depleted mice was significantly shortened (47). Additionally, when prions were inoculated into Il34 -/-mice, which contain fewer microglia because of impaired microglial development and maintenance (48,49), PrP Sc deposition was augmented and prion progression was accelerated in comparison with infected WT littermates (47). Therefore, we contend that microglia play a generally neuroprotective rather than deleterious role in prion pathogenesis ( Figure 2).…”
Section: Microglial Activation and Cytokine Release In Prion Diseasesmentioning
confidence: 99%